Factors Influencing Job Satisfaction of Government Secondary School Teachers in the District of Petaling, Selangor - Su, Chooi Hong (1999)
The main objective of this study was to verify the external and internal conditions influencing job satisfaction among teachers in the district of Petaling, Selangor, by using Herzberg' s Two-Fact or Motivation Theory. The Minnesota satisfaction questionnaire was employed to assess the overall level of satisfaction among the teachers, and the teachers' level of satisfaction with the external and internal conditions of the job. The results revealed that both the internal conditions (motivational factors) and external conditions (hygiene factors) of the job influenced the teachers' job satisfaction. Comparatively, the internal conditions of the job had a slightly stronger influence over job satisfaction than the external conditions (hygiene factors). The motivational factors verified to be related to job satisfaction were the work it self, achievement, recognition, the possibility for growth, and responsibility. For the hygiene factors, status, relationship with the principal, relationship with the colleagues, quality of supervision of the principal, school policy and administration, job security and working conditions were found to be related to job satisfaction. Pay and advancement were found to have little influence on job satisfaction. In general, Herzberg's theory was found to be useful in explaining factors that influenced teachers' job satisfaction.